Ruthenium-doped phosphorized Prussian blue analogue electrocatalyst as well as preparation method and application thereof
By doping ruthenium into the phosphated Prussian blue analogue to adjust its structure and conductivity, the problem of high overpotential of the electrocatalyst in the alkaline oxygen evolution reaction is solved, and efficient electrolytic water catalysis and stability improvement is achieved.
Patent Information
- Application Number
- CN202411391066.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-01-07
AI Technical Summary
The current electrocatalysts have a high overpotential in alkaline oxygen evolution reactions, which limits the efficiency of hydrogen production by electrolyzing water. Especially due to the formation of rigid O-O double bonds and the slow proton-coupled electron transfer process, the catalytic activity is subject to electron mobility. Influence.
By doping noble metal ruthenium into phosphated Prussian blue analog, the nanocube structure and phosphate group content are adjusted, the conductivity and catalytic activity are improved, and the reaction barrier is reduced, and the electrocatalyst electrocatalyst is prepared by doping noble metal ruthenium doped phosphated Prussian blue analogue is prepared. Ru/NiFeP.
The overpotential at 10mA/cm2 current density is significantly reduced to 264mV, which improves the redox reaction activity and the long-term stability of the electrocatalyst, and enhances the catalytic performance of electrolyzed water.
Smart Images

Figure CN119265619A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electrocatalysts, and in particular relates to a ruthenium-doped phosphide Prussian blue analogue electrocatalyst and a preparation method thereof and application thereof in alkaline oxygen evolution reaction.
[0002] The present invention belongs to the 3.1 new functional materials industry key direction in the 3 new materials industry of the catalogue of strategic emerging industries, 3.1.12 new catalytic materials and additives, solid acid catalysts, solid base catalysts, biocatalysts, new petrochemical catalysts, catalysts for chemical, pharmaceutical and environmental protection, new coal chemical catalysts, high-temperature fuel cell catalysts, new photocatalytic materials and other additives. Background Art
[0003] In the field of hydrogen production by water electrolysis, electrocatalytic water splitting is widely used in various hydrogen production technologies due to its zero pollution, simple process and high efficiency. Water electrolysis includes two half reactions: hydrogen evolution reaction (HER) and oxygen evolution reaction (OER). As a key step in the process of water splitting to produce hydrogen, the catalytic efficiency of OER directly affects the energy conversion efficiency. Since OER involves the formation of rigid OO double bonds and slow proton-coupled electron transfer processes, the water electrolysis process is limited by kinetic barriers and high overpotentials. Therefore, people are working hard to develop efficient electrocatalyst materials to promote the OER process.
[0004] Prussian blue analogs (PBA) have shown great potential in the field of electrocatalysis due to their unique structure and rich redox activity. However, due to the interaction between organic ligands and metal ions and the existence of a narrow band gap, the catalytic activity is affected by electron mobility. In recent years, in order to enhance the catalytic performance of PBA, people have explored a variety of strategies such as chemical composition adjustment and structure and morphology optimization. Phosphating, as an effective means, significantly enhances its catalytic activity by improving the conductivity of PBA and thus accelerating electron transfer. Studies have shown that the phosphate group has the ability to regulate and stabilize the state of transition metal intermediates, which helps promote the redox reaction of metal atoms and thus accelerate the water decomposition process.
[0005] For example, the Chinese patent application number 201910026784.8 discloses a method for synthesizing a bimetallic phosphide electrocatalyst with a hollow structure by a self-template method. First, Ni-Fe PBA nanocubes are prepared, and then an etchant monohydrate ammonia solution is selected to etch to obtain Ni-Fe PBA nanocages. The prepared Ni-Fe PBA nanocages are then phosphated with sodium hypophosphite to synthesize a bimetallic phosphide electrocatalyst with a hollow structure. The Ni-Fe PBA nanocages obtained by this preparation method have the advantages of a larger specific surface area, more catalytic active sites, and promoted charge transfer. At 10 mA / cm 2The overpotential is 1.53 V under the current density condition. This overpotential is still relatively high, so the performance of the hollow structured bimetallic phosphide electrocatalyst needs to be further improved.
[0006] In the field of materials science, fusing precious metals with transition metals through technical means such as doping has become an effective new strategy and approach to enhance the catalytic activity of materials. The precious metal Ru exhibits catalytic performance similar to that of platinum, but its cost is only one-fourth of that of platinum. In addition, the rich d-orbital electrons of Ru can improve the surface electronic structure of the phosphide, thereby enhancing its intrinsic activity. Based on the bimetallic phosphide electrocatalyst, the present invention further doped the precious metal Ru to study the effect of the precious metal Ru doping on the activity of the Prussian blue analog electrocatalyst. Summary of the invention
[0007] In view of the above problems existing in the prior art, the present invention provides a ruthenium-doped phosphinated Prussian blue analogue electrocatalyst and a preparation method and application thereof.
[0008] The object of the present invention is achieved in the following manner: A method for preparing a ruthenium-doped phosphinated Prussian blue analogue electrocatalyst comprises the following steps:
[0009] (1) Preparation of NiFe PBA: The molar ratio is 6:
[0010] 9:4Ni(NO 3 ) 2 6H 2 O, sodium citrate and K 3 [Fe(CN) 6 ] are mixed, stirred at room temperature, aged, centrifuged, washed and the yellow precipitate is collected, and dried to obtain the NiFe PBA with nanocube structure;
[0011] (2) Preparation of Ru / NiFe PBA: 1.8-2.2 mg / ml NiFe PBA alcohol solution was mixed with 0.45-0.55 mg / ml RuCl 3 ·3H 2 O aqueous solution, mixed, fully stirred in an oil bath, and dried to obtain Ru / NiFe PBA;
[0012] (3) Preparation of Ru / NiFeP: Ru / NiFe PBA and NaH 2 PO 2 ·H 2 O was placed in two porcelain boats according to the mass ratio of 1:10 and N was placed in a tube furnace. 2 The reaction was carried out at 330-370° C. for 2 h under an atmosphere, and after cooling, a ruthenium-doped phosphide Prussian blue analog electrocatalyst Ru / NiFeP was obtained.
[0013] The specific preparation steps of NiFe PBA in step (1) are as follows: 6 mmol Ni(NO 3 ) 2 6H 2 O and 9mmol sodium citrate were dissolved in 200ml deionized water to form solution A. Then 4mmol K 3 [Fe(CN) 6 ] was dissolved in 200 ml of deionized water to obtain solution B; solution B was then added to solution A, stirred for 10-20 minutes, and then aged for 20-28 hours. Finally, the mixed solution was centrifuged to collect the yellow precipitate, which was washed with water and ethanol, and dried at 55-60°C overnight to obtain NiFePBA.
[0014] In step (1), the centrifuge speed is 9000 rpm, and the collected yellow precipitate is washed three times with water and ethanol respectively.
[0015] The specific preparation steps of Ru / NiFe PBA in step (2) are as follows: dispersing NiFe PBA in ethanol to form a suspension of 1.8-2.2 mg / ml; 3 ·3H 2 O was dissolved in deionized water to obtain 0.45-0.55 mg / ml RuCl 3 ·3H 2 O solution; RuCl 3 ·3H 2 O solution was added to the above suspension, and stirred in an oil bath at 55-60° C. for 1-3 h, and then centrifuged and dried overnight to obtain Ru / NiFe PBA.
[0016] In step (3), the temperature of the tubular furnace is raised to 330-370°C at a rate of 1.5-2.5°C / min and the temperature is kept at this temperature for 2-4 hours.
[0017] A ruthenium-doped phosphide Prussian blue analogue electrocatalyst is prepared by the preparation method.
[0018] The contents of Ru, Ni, Fe and P in Ru / NiFe PBA are 10%, 19%, 18% and 53% respectively.
[0019] Ru / NiFe PBA at 10 mA cm -2 The overpotential at is 264mV.
[0020] Ruthenium-doped Prussian blue phosphide analogue electrocatalyst for alkaline oxygen evolution reaction in water electrolysis for hydrogen production.
[0021] Compared with the prior art, the present invention dopes Ru into NiFe PBA. The precious metal Ru doping can adjust the nanocube structure of NiFePBA, provide abundant active sites, increase the contact area between the electrocatalyst and the electrolyte, and thus improve the catalytic activity. The phosphate group can change and stabilize the state of the transition metal intermediate, ensure the effective redox reaction of the metal atom, accelerate the dissociation of water, and compensate for the low conductivity of NiFe PBA by phosphating to accelerate electron transfer, thereby achieving high catalytic performance. In addition, the electronic synergistic effect between Ru, Ni and Fe regulates the electron density, reduces the reaction barrier, accelerates the dissociation of water, and thus significantly improves the OER activity. The Ru / NiFeP electrocatalyst prepared by the preparation method of the present invention exhibits excellent OER activity and long-term stability in alkaline solution, and the OER activity is 10 mA cm -2 The overpotential at can be as low as 264mV. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 It is the synthesis route diagram of the present invention.
[0023] Figure 2 are transmission electron microscope images of NiFe PBA, Ru / NiFe PBA, Ru / NiFeP, and NiFeP, respectively.
[0024] Figure 3 High-resolution images and energy dispersive spectroscopy images of Ru / NiFeP.
[0025] Figure 4 This is the energy spectrum analysis (EDS) diagram of Ru / NiFeP.
[0026] Figure 5 These are the XRD spectra of NiFeP and Ru / NiFeP and the FT-IR spectra of NiFeP, Ru / NiFeP and Ru / NiFe PBA.
[0027] Figure 6 These are the high-resolution XPS spectra of Ni 2p, Fe 2p, and P 2p of NiFeP and Ru / NiFeP, and the Ru3d spectrum of Ru / NiFeP.
[0028] Figure 7 It is the XRD curve and XPS spectrum of Ru / NiFeP after OER test.
[0029] Figure 8 Ru / NiFeP, NiFeP and RuO 2 OER performance curves, including: (a) LSV curve, (b) overpotential, and (c) corresponding Tafel diagram.
[0030] Fig. 9 is the double layer capacitance (C dl ), electrochemical impedance spectroscopy (EIS) and comparison of the overpotentials of Ru / NiFeP and other PBA materials.
[0031] Fig.10 These are the LSV polarization curves and CP curves of Ru / NiFeP before and after 2000 cycles. DETAILED DESCRIPTION
[0032] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention. After reading the content of the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms also fall within the scope defined by the present invention.
[0033] Example 1
[0034] like Figure 1 As shown, the preparation method of the ruthenium-doped phosphide Prussian blue analog electrocatalyst comprises the following steps:
[0035] (1) Preparation of NiFe PBA: 6 mmol Ni(NO 3 ) 2 6H 2 O and 9 mmol sodium citrate were dissolved in 200 mL deionized water to form solution A; 4 mmol K 3 [Fe(CN) 6 ] was dissolved in 200 mL of deionized water to obtain solution B, which was added to solution A and stirred with a strong magnetic stir for 10 minutes. The mixture was aged for 24 hours, and then the mixed solution was centrifuged at a speed of 9000 rpm to collect the yellow precipitate. The collected yellow precipitate was washed three times with water and ethanol respectively, and dried at 60°C overnight to obtain a nanocubic structured NiFe PBA.
[0036] (2) Preparation of Ru / NiFe PBA: 60 mg NiFe PBA was dispersed in 30 mL ethanol to form a suspension. 10 mL of ethanol containing 5 mg RuCl was added to the suspension. 3 ·3H 2 O and deionized water, the mixed solution was stirred in an oil bath at 60 °C for 2 h, and then the obtained product was centrifuged and dried overnight to obtain Ru / NiFe PBA.
[0037] (3) Preparation of Ru / NiFeP: The Ru / NiFe PBA and NaH 2 PO 2 ·H 2O was placed in two porcelain boats at a mass ratio of 1:10 and N 2 The temperature was raised to 350°C at 2°C / min under a temperature atmosphere, kept at that temperature for 2h, and then cooled to obtain the electrocatalyst Ru / NiFeP.
[0038] Figure 1 The synthesis process of Ru / NiFeP electrocatalyst is shown. 2+ With Fe(CN) 6 3- NiFe PBA nanocubes were obtained by coprecipitation, and Ru was doped on the nanocubes by ion exchange, followed by phosphating to obtain the catalyst.
[0039] Comparative Example 1 Preparation of NiFeP
[0040] The NiFe PBA prepared in step (1) is used as a precursor, and the phosphating step (3) is directly performed without Ru doping in step (2) to synthesize NiFeP.
[0041] Example 2
[0042] The difference from Example 1 is that: step (1) strong magnetic stirring for 20 minutes, aging for 20 hours, and drying temperature is 55°C; step (2) the concentration of NiFe PBA alcohol solution is 2.2 mg / ml, RuCl 3 ·3H 2 The concentration of O aqueous solution was 0.55 mg / ml and stirred in an oil bath at 55°C for 3 h. (3) The heating rate of the tubular furnace was 1.5°C / min, the reaction temperature was 330°C, and the reaction time was 4 h.
[0043] Example 3
[0044] The difference from Example 1 is that: step (1) strong magnetic stirring for 15 minutes, aging for 28 hours, and drying temperature is 58°C; step (2) the concentration of NiFe PBA alcohol solution is 1.8 mg / ml, RuCl 3 ·3H 2 The concentration of O aqueous solution was 0.45 mg / ml and stirred in an oil bath at 58°C for 4 h. (3) The heating rate of the tubular furnace was 2.5°C / min and the reaction temperature was 370°C for 3 h.
[0045] 1. Application of Ru / NiFeP catalyst in oxygen evolution reaction of water electrolysis and investigation of catalytic performance
[0046] Preparation of Ru / NiFeP electrocatalyst solution: 2 mg of catalyst was dispersed in a mixture containing deionized water (120 μL), ethanol (360 μL) and Nafion (20 μL, 5 wt%), and the mixed solution was ultrasonically treated at room temperature for 1 h to obtain a Ru / NiFeP electrocatalyst solution.
[0047] A CHI 660E electrochemical workstation was used in a standard three-electrode system, with Hg / HgO as the reference electrode, a carbon rod as the counter electrode, and a glassy carbon electrode with a diameter of 5 mm and 10 μL of Ru / NiFeP catalyst solution as the working electrode. The potential measured in this work was corrected to the potential under the reversible hydrogen electrode (RHE) according to the formula E(vs.RHE)=E(vs.Hg / HgO)+0.098V+0.059×pH. Before the OER electrocatalytic test, cyclic voltammetry (CV) was used to measure the potential of the catalyst in 1M KOH solution at 30 mV s -1 The activation test was carried out at a scan rate of 5mV s -1 The linear sweep voltammetry (LSV) curve was obtained at a scan rate of 1.5 V, and the polarization curve was not compensated for ohmic drop. The Tafel slope was calculated and fitted based on the LSV curve. The potential range of 0.2 to 0.3 V was varied by different scan rates (20 mV s -1 ~120mV s -1 The double layer capacitance (DLCC) of the prepared material was obtained by CV test. The electrochemical active surface area (ECSA) was estimated based on the DLCC value of the prepared material. The electrochemical impedance spectroscopy (EIS) test was carried out in the frequency range of 10mHz to 100kHz.
[0048] Figure 2 ac are transmission electron microscope images of NiFe PBA, Ru / NiFe PBA, and Ru / NiFeP, respectively. Scanning electron microscopy (SEM) showed that NiFe PBA is a nanocube with uniform size, smooth surface, and an average size of about 100nm. After Ru doping, the surface of Ru / NiFe PBA is slightly rough, but still in a uniform cubic shape. The Ru / NiFeP prepared by phosphating Ru / NiFe PBA has higher roughness and smaller size (less than 100nm) than Ru / NiFe PBA. For comparison, we also synthesized NiFeP without Ru doping, see Figure 2 d, its morphology is still a uniform cube with a rough surface.
[0049] In addition, transmission electron microscopy (TEM) and high-resolution transmission electron microscopy (HRTEM) further demonstrated the morphology and microstructure of Ru / NiFeP. Figure 3 As shown in a, there are a large number of mesopores in Ru / NiFeP, which not only provide channels for electron transfer but also increase the contact area between the catalyst and the electrolyte. Figure 3b is the HRTEM image of Ru / NiFeP, which shows that the lattice spacing on the (211), (201) and (210) crystal planes of NiFeP is 0.167nm, 0.203nm and 0.191nm respectively, and the lattice fringes are clearly visible, indicating that the crystallinity of Ru / NiFeP is high. The energy spectrum analysis (EDS) of Ru / NiFeP confirms the uniform distribution of Fe, Ni, Ru and P. The contents of Ru, Ni, Fe and P are 10%, 19%, 18% and 53% respectively. Figure 4 .
[0050] The structural composition of the samples was analyzed by X-ray diffraction (XRD). The synthesized NiFe PBA matches well with the NiFe PBA standard card (PDF#20-0915), and the crystal structure does not change after Ru doping. Figure 5 As shown in a, after further phosphating the material, NiFeP and Ru / NiFeP present a NiFeP crystal phase (PDF#04-001-4563). Specifically, the diffraction peaks at 40.5°, 44.4°, 47.5°, 54.3°, and 54.9° can be pointed to the (111), (201), (210), (300), and (211) crystal planes of the NiFeP phase, which is consistent with the results of HRTEM. Fourier transform infrared spectroscopy (FT-IR) was also used to analyze the structure of the material. Figure 5 b shows that NiFeP and Ru / NiFeP after phosphating have a wavelength of 900-1200 cm -1 A broad peak appears at PO x , and C≡N at 2098 and 2169 cm -1 The strong peak at becomes significantly weaker. The above results show that NiFeP and Ru / NiFeP successfully undergo phase transformation after phosphating.
[0051] The surface chemical composition and elemental valence state of the samples were characterized by X-ray photoelectron spectroscopy (XPS). In the high-resolution XPS spectrum of Ni 2p in Ru / NiFeP ( Figure 6 a), the peaks at 855.5 and 872.8 eV belong to Ni 2+ 2p 3 / 2 and 2p 1 / 2 orbital, the peaks at 856.8 and 874.4 eV belong to Ni 3+ Ni 2p 3 / 2 and Ni 2p 1 / 2 orbital. The two peaks at 852.8 and 870.1 eV are attributed to the Ni-P bond. Similarly, in the Fe 2p spectrum of Ru / NiFeP ( Figure 6 b), the peaks at 710.3 and 723.7 eV can be attributed to Fe 2+ 2p 3 / 2and 2p 1 / 2 orbital, and Fe 3+ 2p 3 / 2 and 2p 1 / 2 The spin orbits are located at 712.9 and 726.8 eV. In addition, the two peaks located near 708.4 and 720.9 eV correspond to the Fe-P bond, and the peak at 714.7 eV is a satellite peak. It is worth noting that compared with undoped ruthenium NiFeP, the convolution peak positions of Ni 2p and Fe 2p of Ru / NiFeP shifted to higher binding energy by 0.25 and 0.45 eV, respectively. This shift indicates that the local electron density around Ni and Fe is reduced, which helps to reduce the energy barrier and optimize the adsorption of oxygen intermediates and protons.
[0052] exist Figure 6 In the P-2p spectrum of Ru / NiFeP shown in c, the two fitting peaks at 129.7 and 130.7 eV are respectively assigned to the 2p bonds of PM (M = Ni, Fe). 3 / 2 and 2p 1 / 2 , while the peak at 133.7 eV is attributed to the PO bond formed by catalyst oxidation. + The presence of 2- or OH - Compared with NiFeP, it can be observed that 2p 3 / 2 and 2p 1 / 2 The positive shifts are 0.1 and 0.2 eV respectively. The above results show that Ru doping can adjust the electronic structure of Ni, Fe and P, thereby improving the catalytic performance.
[0053] like Figure 6 As shown in d, the peaks of Ru 3d at 280.9 and 284.8 eV belong to Ru 3+ And Ru 4+ The peaks near 531.2 eV and 533.2 eV in the O1s high-resolution spectrum correspond to the Fe(Ni)O bond and H-OH, respectively. The above XPS analysis of the elements in NiFeP and Ru / NiFeP shows that there is a strong electronic interaction between Ru, Ni and Fe, which is beneficial to regulate the chemical environment of the metal site, thereby reducing the energy barrier and promoting the dissociation of water.
[0054] In order to determine whether the structure and chemical composition of Ru / NiFeP have changed, we conducted XRD and XPS tests on it. The results are shown in Figure 7 . After testing, the XRD spectrum ( Figure 7 a) It shows that Ru / NiFeP generates hydroxides (CoOOH and Fe(OH) 3 ). XPS spectrum ( Figure 7bd) shows that Ni, Fe and Ru change from oxidation state (Ni 2+ ,Fe 2+ ,Ru 3+ ) to the reduced state (Ni 3+ ,Fe 3+ ,Ru 4+ ), which may be due to the production of metal oxides or hydroxides. In addition, the disappearance of Ni-P and Fe-P bonds in Ni 2p and Fe 2p indicates that the phosphide has disappeared or converted into other substances, which is further confirmed by the absence of the PM peak in P 2p ( Figure 7 e). O 1s is the same as the previous test result ( Figure 7 f). According to the above results, Ru / NiFeP is converted into hydroxide during the OER process. According to previous literature, metal oxides / hydroxides are considered to be the main active sites in the OER process. Therefore, it is concluded that Ru, Ni and Fe are the main active sites of Ru / NiFeP in the catalytic process.
[0055] In order to demonstrate the catalytic performance of the catalyst of the present invention in electrolyzing water, an electrocatalytic test was carried out in a 1 M alkaline KOH solution using a three-electrode system to evaluate the catalytic performance of Ru / NiFeP.
[0056] In order to compare Ru / NiFeP with NiFeP and commercial catalyst RuO 2 The performance differences of the three catalysts were tested under the same conditions. The overpotential of the catalysts was determined by LSV. The results are shown in Figure 8 .like Figure 8 As shown in b, Ru / NiFeP at 10 mA cm -2 The overpotential at 264 mV is significantly lower than that of NiFeP (290 mV) and RuO 2 (320mV).
[0057] To further evaluate the kinetics of the Ru / NiFeP electrocatalyst, we Figure 8 c compares the Tafel slopes obtained from the corresponding LSV polarization curves. Ru / NiFeP, NiFeP and RuO 2 The Tafel slopes are 105.8mV dec -1 , 120.9mV dec -1 and 151.2mV dec -1 Obviously, the Tafel slope of Ru / NiFeP is the smallest and the OER kinetics of Ru / NiFeP is the fastest.
[0058] The double layer capacitance (C dl) is measured by CV test at different scan rates. Fig. 9 As shown in a, the double layer capacitance (C dl ) is 0.50mF cm -2 , higher than NiFeP (0.14mF cm -2 ). C of Ru / NiFeP electrocatalyst dl The values are linearly correlated with the corresponding electrochemically active surface area (ECSA), which indicates that Ru doping makes the catalysts have more active sites.
[0059] In addition, at 10 mA cm -2 Electrochemical impedance spectroscopy (EIS) was performed at a current density of . Fig. 9 b Nyquist plot of Ru / NiFeP electrocatalyst and NiFeP. It can be seen that the semicircle diameter of Ru / NiFeP is smaller than that of NiFeP (17.8Ω). The value of the semicircle diameter represents the charge transfer resistance (Rct) of the material. Therefore, Ru / NiFeP has a faster charge transfer rate and good conductivity, which is more conducive to the electrolysis of water.
[0060] In addition, the alkaline OER performance of Ru / NiFeP is superior to most of the previously reported PBA electrocatalysts ( Fig. 9 c), thereby improving the electrochemical performance.
[0061] 2. Investigation of the stability of Ru / NiFeP catalyst for water electrolysis
[0062] For water electrolysis catalysts, their stability is another important indicator for evaluating catalyst performance. Fig.10 As shown in a, after 2000 CV cycles, the LSV curve of Ru / NiFeP is slightly offset from the initial curve, but it is within the normal range. In addition, the electrochemical stability of the catalyst was determined by the time potential method (CP). Fig.10 b, After a 20-h test in 1 M KOH solution, the voltage of Ru / NiFeP remained almost unchanged (increased by 20 mV). Therefore, the Ru / NiFeP catalyst has good stability in water electrolysis.
[0063] In summary, we have successfully synthesized a novel Ru-doped PBA phosphide nanocube electrocatalyst with a mesoporous structure. Ru / NiFeP exhibits excellent OER activity and long-term stability in alkaline solution, requiring only 264 mV to drive 10 mA cm -2In addition, detailed mechanistic studies have shown that Ru doping and the synergistic effects of Ru, Ni, and Fe regulate the local electron density and reduce the reaction energy barrier. This study shows that Ru doping and phosphating is an effective strategy to regulate catalyst performance and provides ideas for improving the catalytic activity of other PBA materials.
[0064] The above is only a preferred embodiment of the present invention. It should be pointed out that for those skilled in the art, several changes and improvements can be made without departing from the overall concept of the present invention, which should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a ruthenium-doped phosphinated Prussian blue analogue electrocatalyst, characterized in that: The following steps are included: (1) Preparation of NiFe PBA: Ni(NO3)2·6H2O, sodium citrate and K3[Fe(CN)6] in a molar ratio of 6:9:4 were mixed, stirred at room temperature, aged, centrifuged, washed and the yellow precipitate was collected, and dried to obtain NiFePBA with a nanocubic structure; (2) Preparation of Ru / NiFe PBA: Mix 1.8-2.2 mg / ml NiFe PBA alcohol solution with 0.45-0.55 mg / ml RuCl3·3H2O aqueous solution, stir thoroughly in an oil bath, and dry to obtain Ru / NiFe PBA; (3) Preparation of Ru / NiFeP: Ru / NiFe PBA and NaH2PO2·H2O were placed in two porcelain boats at a mass ratio of 1:10, and reacted at 330-370°C for 2-4 h in a tube furnace under N2 atmosphere. After cooling, the ruthenium-doped phosphide Prussian blue analog electrocatalyst Ru / NiFeP was obtained.
2. The method for preparing the ruthenium-doped phosphide Prussian blue analog electrocatalyst according to claim 1, characterized in that: The specific preparation steps of NiFe PBA in step (1) are as follows: dissolving 6 mmol Ni(NO3)2·6H2O and 9 mmol sodium citrate in 200 ml deionized water to form solution A; then dissolving 4 mmol K3[Fe(CN)6] in 200 ml deionized water to obtain solution B; then adding solution B to solution A, stirring for 10-20 minutes, then leaving it to age for 20-28 hours, and finally centrifuging the mixed solution to collect a yellow precipitate, washing the yellow precipitate with water and ethanol, and drying it at 55-60°C overnight to obtain NiFePBA.
3. The method for preparing the ruthenium-doped phosphide Prussian blue analogue electrocatalyst according to claim 2, characterized in that: In step (1), the centrifuge speed is 9000 rpm, and the collected yellow precipitate is washed three times with water and ethanol respectively.
4. The method for preparing the ruthenium-doped phosphide Prussian blue analog electrocatalyst according to claim 1, characterized in that: The specific preparation steps of Ru / NiFe PBA in step (2) are as follows: dispersing NiFe PBA in ethanol to form a 1.8-2.2 mg / ml suspension; dissolving RuCl3·3H2O in deionized water to obtain a 0.45-0.55 mg / ml RuCl3·3H2O solution; adding the RuCl3·3H2O solution to the above suspension, stirring in an oil bath at 55-60°C for 1-3 h, and then centrifugally drying overnight to obtain Ru / NiFe PBA.
5. The method for preparing the ruthenium-doped phosphide Prussian blue analog electrocatalyst according to claim 1, characterized in that: In step (3), the temperature of the tubular furnace is raised to 330-370°C at a rate of 1.5-2.5°C / min and the temperature is kept at this temperature for 2-4 hours.
6. A ruthenium-doped phosphide Prussian blue analogue electrocatalyst, characterized in that: Prepared by the preparation method described in any one of claims 1 to 5.
7. The ruthenium-doped phosphide Prussian blue analog electrocatalyst according to claim 6, characterized in that: The contents of Ru, Ni, Fe and P in Ru / NiFePBA are 10%, 19%, 18% and 53%, respectively.
8. The ruthenium-doped phosphide Prussian blue analog electrocatalyst according to claim 6, characterized in that: At 10 mA cm -2 The overpotential at is 264 mV.
9. The ruthenium-doped phosphide Prussian blue analogue electrocatalyst as claimed in claim 6 is used for alkaline oxygen evolution reaction.
Citation Information
Patent Citations
Method for synthesizing bimetallic phosphide electrocatalyst with hollow structure through self-template method
CN109647458A